Implementasi Board Game Pembelajaran Etika Kristen “Ethinere” dengan Menggunakan Unity Game Development Engine - Cleming Tedjokusumo; Kristo Radion Purba (Jurnal Infra, 2017)
Currently the game has grown not only in terms of media, but also in terms of goals. The game is currently shifting from its original physical form, now can be played in digital form. The purpose of the game is not only for fun, but also become one of the effective and interactive learning media.Studying is not limited just for academic values, but also ethical ones. To teach ethical values through game media, a Visual Communication Design alumnus has created a board game of ethical Christian learning called “Ethinere”. To create a set of board game “Ethinere”, it takes one million four hundred thousand Rupiah, and the physical form of the game is very easy to missing or damaged.The conclusion of the application made is that fast and stable internet connection has a very important role in application performance, in addition to the numbers of players who play at the same time. Testing login page, lobby, game, result, login map editor, and map editor and its features work as their function.